Impact of Unserviced Loans on Microfinance Banks’ Performance in Nigeria: A Granger Causality Approach (International Journal of Scientific Research and Management (IJSRM), 2025)
Unserviced loan is a major credit risk facing microfinance banks due to their primary role in lending activities. The risk is often associated with more provisions for loan-loss in order to mitigateitsimpact. This study examined the impact of these credit risk variables (unserviced loans and loan-loss provisions) onthe financial performanceof microfinance banks in Nigeria, using the Granger causality approach. Secondary data covering the periods 2012 to 2018, from six purposively selected microfinance banks, was used forthe hypothesized variables in a Vector Autoregressive (VAR) Model.The unit root test was conducted on the data using the Augmented-Dickey Fuller and Phillip-Perron unit roottest, with the aid of the E-VIEW9 statistical software. The resultsrevealed that the variablesare stationary which makes them suitable for the VAR model. Furthermore, the Granger causality analysis was carried out and the results established a causal nexus between the credit risk variables and financial performance to include; a unidirectional causalityflow from non- performing loans to loan-loss provisions and from loan-loss provisions to returns on assets. The study concluded that unserviced loan influences financial performanceamong microfinance banks in Nigeria. Therefore, it was recommended that microfinance banks should regularly and strategically monitor their loan portfolios through the establishment of credit limits at the level of individual borrowers, counterparties or group of counterparties, subject to their own unique credit policies and level of risk tolerance. In addition, policy makers in the banking sector should ensure sound macroeconomic policies, such as inflation and interest rates, which will enhance growth in the microfinance sub-sector.